2010
DOI: 10.1055/s-0030-1249775
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Acteoside Isolated fromCistanche tubulosaon Chemical Mediator Release and Inflammatory Cytokine Production by RBL-2H3 and KU812 Cells

Abstract: The immediate-type allergic reaction is involved in many allergic diseases such as asthma, allergic rhinitis, and sinusitis. In this study, we investigated the effect of acteoside extracted from CISTANCHE TUBULOSA (Schrenk) R. Wight on the basophilic cell-mediated allergic reaction. The effect of acteoside on β-hexosaminidase release and intracellular [Ca (2+)] I level from rat basophilic leukemia (RBL-2H3) cells was determined. Also, ELISA was used to determine the level of histamine, tumor necrosis factor (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…[4,5]. Acteoside has been found to have antioxidative, anti-inflammatory, anti-nociceptive, anti-metastatic, hepatoprotective and cytoprotective activities [6,7,8,9,10,11,12]. Reports have shown that acteoside can alleviate acquired learning disability in mice that is induced by scopolamine [13], and reduce cerebral injury in mice that is induced by d -galactose [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…[4,5]. Acteoside has been found to have antioxidative, anti-inflammatory, anti-nociceptive, anti-metastatic, hepatoprotective and cytoprotective activities [6,7,8,9,10,11,12]. Reports have shown that acteoside can alleviate acquired learning disability in mice that is induced by scopolamine [13], and reduce cerebral injury in mice that is induced by d -galactose [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…β-Hex, which is stored in the secretiory granules of mast cells is released concomitantly with histamine when mast cells are immunologically activated (Ortega et al 1988;Schroeder et al 1995). Thus, β-hex activity in the medium is used as a marker of mast cell degranulation (Yamada et al, 2010). Therefore, RBL-2H3 cells are considered as a good tool for studying the effect of environmental pollutant on chemical mediator release activity.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Cistanche tubulosa (CT) has also been widely used for traditional medication in China. It was reported that CT extract lower the production of TNF-á and IL-4 that are major factors for NO production in inflammatory pathway [19]. …”
mentioning
confidence: 99%